Sosialisasi Bahaya Narkoba Sebagai Upaya Pencegahan Penyalahgunaan Narkoba Di Kalangan Siswa SMPN 4 Watubangga - Ode Asrun Azis, La; Firdaus, Firdaus; Andin, Asmi; fadhillah, Nurul; Tri Utami, Andhini; Istiqamah, Istiqamah; Sridah, Ummul; Sukmi, Nurul Amalia; Jumliana, Jumliana; Arkam Kaslin, Muh. Aidil; Anjani, Rafly; Jufri, Muh; Arnis, Devi (LPPI UMN AL WASHLIYAH, 2024)
Misuse of drugs among adolescents is increasingly affected, including in rural areas such as Polenga Village, Watubangga Sub-district, Kolaka Regency. Teenagers, especially junior high school students, are very vulnerable to the negative influence of drugs due to a lack of knowledge and information related to the dangers of drugs. A Community Service Program (PKM) of Higher Education Excellence on the dangers of drugs is needed to increase students' awareness of the threat of drugs and encourage their prevention. This PKM program aims to provide an in-depth understanding of the types of drugs, the adverse effects of use, and prevention strategies. This evaluation and monitoring activity was carried out using lecture methods, interactive discussions, and distribution of educational materials. Based on the evaluation, this activity succeeded in increasing students' understanding of the dangers of drugs and encouraging positive behavior to stay away from drugs. It is hoped that this activity can be sustainable and scaled up to cover more schools and communities in other areas.